Permissible and Prohibited Businesses in Islam - Intes, Amina; Barroso, Uwe; Mark, Eladdadi (Yayasan Pendidikan Islam Daarut Thufulah, 2023)
Business is a very important thing in the economy, Islam sees business as having to be done but must comply with the rules that have been regulated in islam. This article aims to provide information to readers both student who are prospective entrepreneurs, prospective entrepreneurs/ wati so they can understand in theory how they should and should be a businessman in accordance with Islamic teachings. And it is also hoped that this writing will become an enlinghtenment for traders and entrepreneurs. The research method used in this article is descriptive qualitative. The descriptive qualitative technique used is library research, which is data collection by conducting study studies of books, literature, notes, and reports that have to do with the problem being solved. This research also examines written sources such as scientific journals, reference books, literature, etc. related to research studies. And the results of this study are that there are some values that must be applied by business people in doing business including honesty, fairness, oneness, honesty in business, honesty in production, honesty in selling, honesty in gaining profit. While the value in justice is fairness in business, justice in production, fairness in selling, justice in gaining profit. And the next value is the value of oneness, namely oneness in production, oneness in selling and oneness in gaining profit.